Indicative features of tissue and microbial sensitization in the pathogenesis of generalized parodontitis associated with rheumatoid arthritis - Proschenko, A.M.; Proschenko , N.S.; Reshetnyk , L.L.; Zelinskaya, N.A.; Chervonna , N.V.; Melnychyk, T.A. (Medicni Perspektivi, 2024)
In the literature, there are not enough studies that reflect the role and place of tissue and microbial sensitization in patients with generalized parodontitis (GP) associated with rheumatoid arthritis (RA). In our opinion, the research of these components will help to better understand the etiopathogenetic mechanisms of development of GP against the background of RA, which will improve the formation of preventive and therapeutic measures for this disease treatment. The purpose of the research was to determine the location and integration features of tissue and microbial sensitization in the pathogenesis of generalized parodontitis associated with rheumatoid arthritis. Immunological studies were carried out in 335 people, who were divided into 4 groups: Group 1 – the main – consisted of 136 patients with GP on the background of RA; Group 2 – control – 71 people with GP without signs of RA; Group 3 – comparison – 128 people without GP, but with diseases of the musculoskeletal system not related to RA and Group 4 – 30 practically healthy people. To determine microbial and tissue sensitization, we used inhibition reaction of migrating lymphocytes with microbial antigens of streptococci and staphylococci, tissue antigens (bone and synovial). A high frequency of microbial sensitization to streptococcal and staphylococcal antigens was established in patients with GP on the background of RA and in patients with GP without signs of RA. The parodontal focus turned out to be an active focus of microbial sensitization in patients with GP associated with RA and in patients with GP without signs of RA. Established sensitization to bone antigen in a small number of patients (27-33%) with GP, which was significantly more frequent (61-80%) in patients with GP associated with RA, indicates that in the latter, allergy is to a greater extent due to tissue systemic damage to connective tissue than GP. However, a certain allergy to bone tissue in GP may indicate the inclusion of an immune component in the pathogenesis of GP. The presence of microbial and tissue sensitization in patients with GP and RA indicates that similar and cross antigens of streptococcal and staphylococcal microorganisms with connective tissue are a potential trigger for the development of both GP and RA, which is a reason to consider GP and RA comorbid diseases with similar pathogenetic mechanisms of development.